Music and Gesture—New Perspectives in Conducting and in Education - Riccardo Lombardo (Creative Arts in Education and Therapy)
The inspirational theory for this research is Rudolph Laban’s method of analysis of movement, including further developments of the theory. Bartee’s theoretical paper, “Organizational Development: Theory, Practice, and Research,” opened a new perspective on the art of conducting, proposing a new expressive style, based on Laban’s theory. Starting from that point of view, my research, held with a group of students of the Faculty of Education at the University of Valladolid (Spain), involved the analysis of videos of the students conducting a piece. The videos were recorded before and after a workshop on creative movement using the García-Plevin® method. Both the researcher and the group took over the data collection, through direct and indirect observation of the tests and qualitative and quantitative approaches. The most interesting results affect, among others, the self-confidence and the use of kinesphere in controlling beat, dynamics, rhythm, agogics (tempo indications and variations), and phrasing.